ATTITUDE OF SENIOR SECONDARY SCHOOL STUDENTS TOWARDS AGRICULTURAL SCIENCES AND TRAININGS IN OGBOMOSO NORTH LOCAL GOVERNMENT AREA OF OYO STATE - J.O., Akintonde; O.A., Akinboye; A.O., Tiamiyu; O.S., Akintaro; S.A., Gbadamosi; B.S., Bamidele; A.A., Alabi (International Journal of Research -GRANTHAALAYAH, 2019)
The study assesses the attitude of senior secondary school students towards agriculture as a profession in some selected secondary schools in Ogbomoso North Local Government Area of Oyo State. One hundred respondents were randomly selected from five senior secondary schools purposively selected due to their questionnaire. The data obtained were analyzed with the aid of frequency count, percentages and cumulative percentage while correlation analysis was used to test the hypothesis. The findings reveal the personal characteristic of the respondents sampled as well as their level of interest in agriculture as a profession. The statistical analysis performed on the respondents’ attitude towards agriculture as a profession revealed that there was significant relationship to the respondents’ gender, educational level father and mother’s occupation respectively while age and religion were statistically insignificant.